Color Analysis on Natural Polyphenolic Dyed Cotton Cellulose Fibers (Journal of Fiber Bioengineering and Informatics, 2018)
Natural polyphenolic dye extracted from green tea is used to dye cotton cellulose fibers. FTIR for the microstructure analysis of fibers, and SEM for the surface morphology observation have been used to characterize the changes induced by tea dyeing. Color shade, thermal stability and mechanical property of dyed fibers are tested. The results show that hydroxyl group of tea polyphenolic and cotton cellulose forms hydrogen bond in dyed fibers without mordant agent, while both coordinate bond and hydrogen bond are coexisted in meta-mordant dyed fibers. The deep shade is obtained in acid media of pH 4 for meta-mordant dyed fibers due to the mordant effect. The coordinate bond contributes to the thermal stability of meta-mordant dyed fibers. The formation of fiber-Fe complexation decreases tensile strength and increases elongation at break for fibers.
Keywords: Cotton cellulose fiber; natural polyphenolic dyestuff; green tea; iron ion; thermal stability; tensile property